Building Urban Resilience: Principles, Tools, and Practice - Jha, AbhasK. (World Bank, 2015)
Resilience is the ability of a system, community, or society exposed to hazards to resist, absorb, accommodate to, and recover from the effects of a hazard in a timely and efficient manner. Resilience in the context of cities translates into a new paradigm for urbanization, and forms base for a new understanding how to manage hazards and urban development. In the next decades, the major driver of the increasing damages and losses from disasters will be the growth of people and assets in harm?s way, especially in urban areas. Often lacking resources, infrastructure, services and the capacity to manage the increase in population, small cities could face heavy losses of life and property due to disasters, unless proactive measures are mainstreamed into governance and planning.